On the extremality of non-standard maximal dual feasible functions - Rietz, Jurgen Endre (2013)
Dual feasible functions were successfully used as a fast tool to get lower bounds for bin packing problems for a long time. Here they are investigated with respect to extremality for the domain R and also the higher-dimensional domain [0; 1]m with m 2 N;m > 1. Both situations are generalizations of the already known domain [0; 1].